PEWARISAN NILAI SEJARAH LOKAL MELALUI PEMBELAJARAN SEJARAH JALUR FORMAL DAN INFORMAL PADA SISWA SMA DI KUDUS KULON - Amin, Syaiful (Paramita: Historical Studies Journal, 2011)
This research is conducted in the community of Kudus Kulon and High Schools in Kudus. Data collection techniques used in this research are in-depth interviews, observation, and content analysis. Data validation is triangulation of data and triangulation of method. Analysis of data is done through an interactive analysis with the three stages of analysis, namely data reduction, data presentation, and drawing conclusion that interact with the data collection cycle. The results showed that: (1) Teacher implemented inheritance of value through formal history learning, but the result shows it is no more optimal because of time allocation problem; (2) Inheritance of value in informal history learning occurs through folklore which is told in the family and society as a religious ritual events, (3) Continuity history learning through formal and informal channels occurs because of mutually reinforce relationship that makes the efforts of inheritance so the maximum value of local history ÃÂ Key words: local history, inheritance of value, formal and informal education, kudus kulon ÃÂ